Henry Smeathman, the flycatcher : natural history, slavery and empire in the late eighteenth century - COLEMAN, DEIRDRE (Romantic reconfigurations., 2018)
This book enriches our understanding of Romanticism and colonialism by telling the story of Henry Smeathman (1742-86), natural historian and sentimental traveller whose extraordinary life in West Africa and the West Indies provides us with vivid, eye-witness accounts of Atlantic slavery, the Middle Passage, and the difficulties of collecting in the tropics.